2018
DOI: 10.21273/jashs04424-18
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Transcriptome Data for Enhanced Gene Expression Analysis in Apple

Abstract: Complex changes in gene expression occur during postharvest storage of apple (Malus ×domestica) and often precede or accompany changes in ripening and disorder development. Targeted gene expression analysis fundamentally relies on previous knowledge of the targeted gene. Minimally, a substantial fragment of the gene sequence must be known with high accuracy so that primers and probes, which bind to their targets in a complimentary fashion, are highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Candidate genes and their primer characteristics can be found in S5 Table in S4 File (CDS and primer alignments in S2 File ). Reference genes previously used in [ 56 ] and [ 4 ] were selected from the literature: MDP0000274900 [ 57 ], MDP0000173025 [ 58 ], and MDP0000223691 [ 59 ]. The GDDH13 homologous sequences for these reference genes were identified, using PlantTribes2, as MD09G1190100, MD16G1209000, and MD15G1211100 respectively [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate genes and their primer characteristics can be found in S5 Table in S4 File (CDS and primer alignments in S2 File ). Reference genes previously used in [ 56 ] and [ 4 ] were selected from the literature: MDP0000274900 [ 57 ], MDP0000173025 [ 58 ], and MDP0000223691 [ 59 ]. The GDDH13 homologous sequences for these reference genes were identified, using PlantTribes2, as MD09G1190100, MD16G1209000, and MD15G1211100 respectively [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…W4502; Sigma-Aldrich, St. Louis, MO) to produce 100 μm solutions, and stored at –20°C. qPCR was performed as described in [ 56 ] for ‘Granny Smith’ on a subset of 33 Year 2 samples (corresponding to similar early and late postharvest storage time points from each experimental treatment and condition in Year 1—S6 Table in S4 File ) with a slight modification to the protocol: the qPCR reaction volume was increased to 15 μL [to accommodate automated liquid handling by an epMotion 5073 (Eppendorf, Hamburg, Germany)] by increasing the volume of SYBR per reaction while maintaining the template mass per reaction (10 pg cDNA).…”
Section: Methodsmentioning
confidence: 99%
“…A principle components analysis ( Supplementary Figure 1 ) of our pilot GEM (peel data) revealed that the transcriptome data had sufficient structure to distinguish fruit based on canopy position and tissue, thus providing contrasts to explore molecular signatures of differential ripening between canopy positions, as well as search for possible biosignatures. We selected genes for qPCR validation following Hargarten et al (2018) and the validation showed an average R 2 of 0.72 for the linear regression of all independent biological replicates ( R 2 = 0.83 for means) across a subset of samples for the each of the 10 candidate genes ( Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq estimates of gene activity were then validated on a subset of genes via qPCR. The subset of genes selected was based on the workflow described in Hargarten et al (2018) . The following criteria were used to select genes: (1) cumulative reads per kilobase transcript per million reads (RPKM) ≥ 2,000 ( n = 1,830 genes), (2) standard deviation between 50–100 RPKMs ( n = 47), (3) linear relationship with time in a subset of samples ( n = 19), (4) high identity matches between de novo ‘d’Anjou’ transcripts and Bartlett genome reference.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation